Tracing Multifaceted Gastronomic Changes in Joanne Harris’ Food Trilogy - ., Vaishnavi; M, Senguttuvan (Journal of Cultural Analysis and Social Change, 2025)
Food is the essence of life. As Passariello (1990) so eloquently said, its nature is “…somehow, simultaneously, both itself and more than itself.” It is intricately linked to an individual’s social, cultural, and political identity, while it also transcends borders, corporeal as well as metaphorical. Moreover, the use of food in literature transforms the narrative along with the lives of the characters. This paper intends to analyze Joanne Harris’ Chocolat (1999), Blackberry Wine (2000), and Five Quarters of the Orange (2001) through her use of food as a means of showcasing the transformation and reconstruction of identities and relationships. It examines her entangled use of the culinary to reflect the lives of characters living in troubled societies. It also brings forth Harris’ unmatched ability to cook narratives that are sown with trouble but bloom and harvest into incontestable transformations. Furthermore, it examines the myriad ways that Harris uses the analogy of food to bring about changes. Additionally, the research explores the use of the kitchen space and food to showcase character transformations. It also delves into how food is used to form and nourish relationships, be they familial, societal, or intergenerational. The way food is physically ingested, digested, and transformed into nutrition for the body, Harris employs the same in a metaphorical sense.